Comparative Study between the Thai and Hong Kong Fine Gold Jewelry Export Industries - Nithisathian, Kittichok (Information Management and Business Review, 2011)
The Thai fine gold jewelry export industry is a subsector of the gem and jewelry industry that is Thailand’s third most important export category and the leading sector of the creative industry. This industry creates little pollution, is in line with the nature of the Thai people, brings foreign currency into Thailand and creates both high value added and much employment. The growth rate for exports in this sector has decreased due to the economic downturn, fluctuating raw material costs, the unstable political situation in Thailand, lack of investment in technology by Thai manufacturers and the arrival of new entrants from China and India. It is important for Thai exporters to understand the situation they face so as to remain competitive. This paper reports on research conducted by in-depth interviews to identify key issues uniting and dividing Thai and Hong Kong Fine Gold Jewelry Exporters. It is shown that, in terms of new product development, Thai manufacturers should focus more on the marketing orientation rather than personal judgment. Only products that come with the right concept benefit from value added. Thai exporters should focus on product development, networking, be risk takers and foster cooperation between Thai organizers for international gems and jewelry fairs, while also lobbying for a long term government support plan.